Genotoxicity testing approaches for the safety assessment of substances used in food contact materials prior to their authorization in the European Union. (28th May 2017) - Bolognesi, Claudia; Castoldi, Anna F.; Crebelli, Riccardo; Barthélémy, Eric; Maurici, Daniela; Wölfle, Detlef; Volk, Katharina; Castle, Laurence
Abstract : Food contact materials are all materials and articles intended to come directly or indirectly into contact with food. Before being included in the positive European "Union list" of authorized substances (monomers, other starting substances and additives) for plastic food contact materials, the European Food Safety Authority (EFSA) must assess their safety "in use". If relevant for risk, the safety of the main impurities, reaction and degradation products originating from the manufacturing process is also evaluated. Information on genotoxicity is always required irrespective of the extent of migration and the resulting human exposure, in view of the theoretical lack of threshold for genotoxic events. The 2008 EFSA approach, requiring the testing of food contact materials in three in vitro mutagenicity tests, though still acceptable, is now superseded by the 2011 EFSA Scientific Committee's recommendation for only two complementary tests including a bacterial gene mutation test and an in vitro micronucleus test, to detect two main genetic endpoints (i.e., gene mutations and chromosome aberrations). Follow‐up of in vitro positive results depends on the type of genetic effect and on the substance's systemic availability. In this study, we provide an analysis of the data on genotoxicity testing gathered by EFSA on food contact materials for the period 1992–2015. We also illustrate practical examples of the approaches that EFSA took when evaluating "non standard" food contact chemicals (e.g., polymeric additives, oligomer or other reaction mixtures, and nanosubstances). Additionally, EFSA's experience gained from using non testing methods and/or future possibilities in this area are discussed. Environ. Mol. Mutagen. 58:361–374, 2017. © 2017 Wiley Periodicals, Inc.